2007
DOI: 10.1074/jbc.m702299200
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor β1-regulated Xylosyltransferase I Activity in Human Cardiac Fibroblasts and Its Impact for Myocardial Remodeling

Abstract: In cardiac fibrosis remodeling of the failing myocardium is associated with a complex reorganization of the extracellular matrix (ECM). Xylosyltransferase I and Xylosyltransferase II (XT-I and XT-II) are the key enzymes in proteoglycan biosynthesis, which are an important fraction of the ECM. XT-I was shown to be a measure for the proteoglycan biosynthesis rate and a biochemical fibrosis marker. Here, we investigated the XT-I and XT-II expression in cardiac fibroblasts and in patients with dilated cardiomyopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 43 publications
(44 reference statements)
7
60
1
Order By: Relevance
“…79,80 Their importance is suggested by the increased expression of xylotransferase I, the enzyme responsible for attaching the GAG tertrasaccharide linker unit, and CS in patients with dilated cardiomyopathy. 75 This upregulation is also seen in fibroblasts stimulated with TGF-β or subjected to mechanical stress. 75 Some experimental studies support a potential role for GAGs in cardiac remodeling after MI, demonstrated by the increase of CS and DS expression in myocardial scars of dogs and rats.…”
Section: Circulation Researchmentioning
confidence: 91%
See 1 more Smart Citation
“…79,80 Their importance is suggested by the increased expression of xylotransferase I, the enzyme responsible for attaching the GAG tertrasaccharide linker unit, and CS in patients with dilated cardiomyopathy. 75 This upregulation is also seen in fibroblasts stimulated with TGF-β or subjected to mechanical stress. 75 Some experimental studies support a potential role for GAGs in cardiac remodeling after MI, demonstrated by the increase of CS and DS expression in myocardial scars of dogs and rats.…”
Section: Circulation Researchmentioning
confidence: 91%
“…cardiac remodeling, 75 more specifically in cardiac hypertrophy, 76 age-related degeneration of the myocardium, 77,78 and MI. 79,80 Their importance is suggested by the increased expression of xylotransferase I, the enzyme responsible for attaching the GAG tertrasaccharide linker unit, and CS in patients with dilated cardiomyopathy.…”
Section: Circulation Researchmentioning
confidence: 99%
“…Recent studies have shown that cardiac fibrosis is a process characterized by massive remodeling of the myocardial extracellular matrix and subsequent substitution of functional tissue by inelastic fibrotic tissue leading to failing heart. 27,28 Vanhoutte et al 29 demonstrated that syndecan-1, which is a transmembrane (type I) heparan sulfate proteoglycan and is a member of the syndecan proteoglycan family, plays a pivotal role in protection against exaggerated inflammation and adverse infarct healing after myocardial infarction in mice. Moreover, Hong et al 30 showed that supplementation with dermatan sulfate, a glycosaminoglycan, improved cardiac function and maintained viability of cardiac myocytes with complement activation.…”
Section: Discussionmentioning
confidence: 99%
“…At a mechanistic level, TGF-β was shown to up-regulate xylosyltransferase-1, i.e. a rate-limiting enzyme that initiates CS attachment onto PG core protein (41) and GalNAc 4-O-sulfotransferase (42,43) that catalyzes one of the key steps in CS-56 epitope formation. Our group is currently investigating whether CS induction constitutes an important down-stream event of the TGF-β signalling pathway during epithelial-mesenchymal transition and cancer progression.…”
Section: Discussionmentioning
confidence: 99%